Whitefly population in shaded tomato field - Sánchez, Daniel; Scotta, Roberto; Arregui, Cristina (Pesquisa Agropecuaria Brasileira, 2005)
In Santa Fe, Argentina, whitefly (Trialeurodes vaporariorum, Westowood) (Hemiptera: Aleyrodidae) populations were monitored during summer in shaded and non shaded tomato field. Tomato was transplanted in rows and half of crop surface was shaded with a black polypropilen layer. Whitefly population was monitored at three-day intervals in 30 plants. Adult whiteflies were surveyed in the highest developed leaf and immature stages in 10 random leaflets in each plant. Experimental design was in randomized blocks and the correlation was calculated among temperature and number of adults and nymphs. In shaded tomato, temperature was lower but whitefly adult populations increased ten times and immature stages increased five times.